2022
DOI: 10.1097/corr.0000000000002279
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Oximetry Does Not Reliably Predict Wound-healing Complications in Preoperatively Radiated Soft Tissue Sarcoma

Abstract: Background Surgical wound-healing complications after tumor resections in tissue that has been preoperatively radiated are a major clinical problem. Most studies have reported that complications occur in more than 30% of patients undergoing such resections in the lower extremity. There is currently no available method to predict which patients are likely to have a complication. Transcutaneous oximetry has been identified in preliminary studies as potentially useful, but the available evidence on its efficacy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…A prospective, multi-institution study from Cleveland (Ohio, USA) measured skin oxygenation at three timepoints in 39 patients undergoing surgery for a lower extremity soft-tissue sarcoma after preoperative radiation. 3 The authors identified no difference in the odds of a wound-healing complication between patients whose transcutaneous oxygen measurements were ≥ 25 mmHg at all timepoints compared with those who had one or more readings below that threshold. Furthermore, there was no difference in the odds of a wound-healing complication between patients who had recovery of skin oxygenation between radiation and surgery and those who did not.…”
Section: Transcutaneous Oximetry and Wound Healingmentioning
confidence: 96%
“…A prospective, multi-institution study from Cleveland (Ohio, USA) measured skin oxygenation at three timepoints in 39 patients undergoing surgery for a lower extremity soft-tissue sarcoma after preoperative radiation. 3 The authors identified no difference in the odds of a wound-healing complication between patients whose transcutaneous oxygen measurements were ≥ 25 mmHg at all timepoints compared with those who had one or more readings below that threshold. Furthermore, there was no difference in the odds of a wound-healing complication between patients who had recovery of skin oxygenation between radiation and surgery and those who did not.…”
Section: Transcutaneous Oximetry and Wound Healingmentioning
confidence: 96%
“…In the current study, Nystrom et al [9] prospectively assessed skin oxygenation in patients undergoing surgery for lower extremity soft tissue sarcoma after preoperative radiation at three timepoints (before radiation, right after radiation, and within 24 hours before the surgery), which were selected based on the rationale that radiotherapy would predictably interfere in a time-dependent fashion with skin oxygenation. They found no benefit from measurement of transcutaneous oxygen tension (TcO 2 ) in anticipating wound complications, using a TcO 2 reading with a cutoff of 25 mmHg and as a continuous variable.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Despite the obvious relationship between hypoxia and wound breakdown, numerous variables may have contributed to this null result. As pointed out by the authors [9], transcutaneous oximetry provides limited focal sampling and, despite the use of multiple leads, only a small portion of the wound surface is assessed. In addition, even with the standardized radiation regimen of 50 Gy in 25 fractions they used for all patients, variability in tumor volume and anatomic compartment may cause differences in the volumetric conformity during the radiation treatment plan (radiation conformity index), extent of radiated skin, and relationship with the incision site and length.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The destruction of the skin's barrier function causes bacterial infection, leading to wound ulceration and delayed recovery, 3 even fatal complications such as sepsis, necrotizing pneumonia, endocarditis, and other infection-related diseases. 4 For third-degree burns, the most common and most serious kind of burns, 5 the central issue of treatment is promoting wound healing and reducing the incidence of burn infection. 6,7 Curcumin is a natural source drug and has a good wound healing effect.…”
Section: ■ Introductionmentioning
confidence: 99%